Teachers’ Perception Toward Assessing Students Based On 21st-Century Skills - Sandiyani, Ni Luh Kupit; Padmadewi, Ni Nyoman; Artini, Luh Putu (Universitas Pendidikan Ganesha, 2022)
This study aimed to analyze the teachers’ perception in assessing the implementation of the 21st-century skills, in Private Elementary schools in Badung Regency. This study used mixed method research design. There were two schools as the representatives of Private Elementary schools in Badung Regency. This study analyzed the teachers’ readiness in assessing the students’ 21st-century skills. Four teachers were selected using a convenient sampling method. The instruments used in this study comprised questionnaires, anecdotal records, and interview guides. It was found that English teachers in both schools have positive responses toward inserting 21st-century skills in their assessment. This is indicated by the mean score of the respondents’ responses which means that the teachers perceived themselves as being ready in inserting the skills into their assessment. The score falls into the category of high level of readiness as they feel that they had inserted most of the skills in the assessment instruments used to assess their students’ English language learning.